GAYA KEPEMIMPINAN KEPALA SEKOLAH DI PAUD KB ALMALIKI DAWUHAN LOR SUKODONO LUMAJANG - Putra, Wijaya Adi; Utami, Riza Wahyu; Jamilah, Nurul (Dharmas Education Journal (DE_Journal), 2024)
Leadership styles applied by elementary school principals in each of these regions. Researchers chose the Almaliki Dawuhan Lor Sukodono Lumajang KB Preschool which is in Dawuhan Lor Sukodono Lumajang Village. The aim of this research is to determine the leadership style applied by the principal at PAUD KB Almaliki Dawuhan Lor Sukodono Lumajang. There are 4 types of leadership styles that may be applied by school principals, namely autocratic, laissez-faire, democratic and pseudo-democratic. This research is qualitative research using the descriptive method with the research location at PAUD KB Almaliki Dawuhan Lor Sukodono Lumajang, starting in July 2023 with the research subjects being principals, teachers, committee members and school supervisors respectively. This research data was obtained from interviews, observation and documentation. The data that has been collected is then tested for validity by testing credibility, transferability, dependability and confirmability. Next, the data was analyzed using an interactive model whose analysis process was divided into 4 stages, including data collection, data reduction, data presentation and ending with drawing conclusions. Based on the analysis of research data that has been carried out, the results of the research show that the leadership style applied by the principal at PAUD KB Almaliki Dawuhan Lor Sukodono Lumajang is a democratic leadership style that always emphasizes openness of information, freedom of opinion, controlled freedom in carrying out learning, and togetherness. -Equally with all parties in every decision making.